PTU-178 The clinical effectiveness of a low fodmap dietary approach in clients with functional gut disorder. (22nd June 2015) - Mccamphill, C; Morrison, G
Abstract : Introduction: To assess the clinical effectiveness of a Low FODMAP diet in clients referred with functional gut disorder. Method: Funding was sought to set up a Low FODMAP pilot clinic, 3.5 h per week for six months. A local protocol and care pathway was developed by the author. Potential clients were referred by the Consultant Gastroenterologist. An audit template developed and completed. Results: 19 Clients where recruited to the pilot phase. There was an overall 88% adherence to the three appointment care pathway. There was reduced use of antispasmodics, anti-diarrhoeals and laxatives from appointment one to appointment three. 56.3% of clients had the symptoms >10 years, with 100% having the symptoms more than 1 year. Thus it is very important to build a good rapport and relationship with the client from the start. The author does feel that the carepathway designed, of 3 appointments with 1 h long sessions, is essential in building this relationship. As IBS is known to be a relapsing condition it is important that all education is given accurately to prevent the client from re-entering the healthcare system at a later date. 64% of clients reported following the diet >75% of the time. 67% of clients reported having overall satisfactory relief of gut symptoms at appointment two, with 71% reporting overall satisfactory relief of gut symptoms at appointment three. The individual patient satisfaction questionnaire results at the 3 rd appointment exhibited: 85% improved in bloating, 78% improved in abdominal/discomfort, 77% flatulence/wind improvement, 69% diarrhoea improvement, 46% improvement in constipation, 46% improvement in nausea and 62% improvement in energy. Only 13% of clients were re-referred back to the Consultant Gastroenterologist. Conclusion: Overall, 88% of clients completed the carepathway within the designated time. Only 13% were re-referred back to the Consultant Gastroenterologist for further investigation/treatment options. 71% of clients who completed the carepathway reported overall satisfactory relief of gut symptoms. Disclosure of interest: None Declared. References: Staudacher HM, Whelan K, Irving PM, Lomer MCE. Comparison of symptom response following advice for a diet low in fermentable carbohydrates (FODMAPs) versus standard dietary advice in patients with Irritable Bowel Syndrome. J Hum Nutr Diet 2011;24:487–495 Barrett JS, Gearry RB, Muir JG, Irving P, Rose R, Haines M, Shepherd SJ, Gibson PR. Dietary poorly absorbed, short-chain carbohydrates increase delivery of water and fermentable substrates to the proximal colon. Aliment Pharmacol Ther. 2010;31:874–882 Maxion-Bergemann, et al . Costs of irritable bowel syndrome in the UK aned US. Pharmacoeconomics 2006;24(1):21–37